Does Carotid Atherosclerosis Cause Tinnitus? - Güven Yıldırım; Özlem Keskin; Kürşat Murat Özcan; Tolgar Lütfi Kumral (Haseki Tıp Bülteni)

(untitled)
Aim:Atherosclerosis is a disease affecting the intimas of arteries. We aimed to investigate the presence of carotid atherosclerosis in patients with tinnitus as an etiologic factor of tinnitus.Methods:A total of 73 patients were included. The patients were divided into 4 groups according to the degree of sclerosis. Triglyceride, total cholesterol, high-density lipoprotein (HDL) and low-density lipoproteins (LDL) levels were investigated. Tinnitus was questioned in patients. All patients have undergone a pure tone audiometry. Comperative statistical analysis was performed.Results:Tinnitus was seen in 79.5% of the patients and 20.5% of the patients had no tinnitus. Carotid stenosis of 1-49% degree was present in 16.4%, of 50-69% degree was present in 21.9%, and of 70% degree was present in 30.1% of the patients while 31.5% of the patients had no carotid stenosis. No significant association was present between carotid stenosis and the presence of tinnitus. HDL levels in patients with carotid stenosis of 1-49% degree were significantly higher than in those without stenosis. No significant difference was found between audiogram data and the level of carotid stenosis.Conclusion:There was no significant relationship between the degree of carotid stenosis and the presence of tinnitus. Mean HDL levels were higher in carotid artery stenosis of a 1-49% degree.